Síntese, caracterização espectroscópica e avaliação antioxidante de derivados de furanochalcona. - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2021)
Chalcones are a class of flavonoids and are associated with various biological activities, are widely studied by the pharmaceutical industry. The furanchalcones are analogous compounds such as chalcones, they replace or insert a furan group in its structure in place of one of the benzene rings. This structural modification provides similar or even different biological functions for such compounds, which continues to make them attractive from a scientific point of view. They are structures that are obtained synthetically and characterized by Nuclear Magnetic Resonance (NMR) spectroscopy. This project aimed to synthesize a series of five furanchalcones, with the following substituants in position or to the aromatic ring: hydroxyl, nitro, bromine and hydroxyl with the nitro group in position 5, in addition to furanchalcone without substitutter. As synthesis, they were assisted by ultrasound, using the cavitation phenomenon for the activation of the reaction. Observing the results of the characterization by one-dimensional and two-dimensional NMR, the efficacy of the use of the use of ultrasound was demonstrated with the absence of interfering signs of impurities, leftovers of reagents or by-products. All compounds were obtained with satisfactory yields. In the biological evaluation, it was to analyze the antioxidant power of the substances, that is, their ability to prevent oxidation and/or inhibit possible free radicals, since these free radicals are associated with several pathologies. Using the radical DPPH sequestration methodologies and the methodology for reducing the phosphomolybdenum complex. From the analyses, it was observed better results for the compounds replaced with the hydroxyl and nitro group, correlating the two techniques used and performing comparisons with the quercetin pattern, furanchalcone without substitut and a traditional chalcona without substitutum.
Keywords: Síntese orgânica; furanochalcona; atividade antioxidante; Organic synthesis; furanchalcones; antioxidant activity; CNPQ::CIENCIAS EXATAS E DA TERRA::QUIMICA